Antimicrobial potential of various extract and fractions of leaves of Solanum - Muhammad Zubaır; Komal Rızwan; Nasır Rasool; Nosheen Afshan; Muhammad Shahid; Viqar uddin Ahmed (International Journal of Phytomedicine, 2011)
This study was carried out to evaluate the antimicrobial activity of methanolic extract and different fractions (n-butanol, ethyl acetate, chloroform and n-hexane) of S.nigrum leaves. The antimicrobial activity was determined by the disc diffusion method and minimum inhibitory concentration (MIC) against a panel of microorganisms (four bacterial strains, i.e P. multocida, E. coli, B. subtilis and S. aureus and three fungal strains, i.e A. flavus, A. niger and R. solani).The results indicated that leaf extract and fractions of S. nigrum were mildly potent as antibacterial agent. While Antifungal activity of S. nigrum leaves extract/fractions was poor.